Green cosmetics: perspectives and challenges in the context of green chemistry - Franca, Camilla Custoias Vila; Ueno, Helene Mariko (Desenvolvimento e Meio Ambiente, 2020)
Green cosmetics present ecological appeals and claim to be developed according to the principles of Green Chemistry. Green Chemistry can be defined as the set of processes and products that reduces or eliminates the use or generation of hazardous substances. Despite the growing market, there are gaps related to the scope and regulation of these products. The article consists of a literature review on conceptual, regulatory and risk analysis limitations and perspectives of green cosmetics. We conducted searches in databases of scientific articles and analysis of publications by government agencies and organic/natural cosmetic certification systems. From the data collected, we found that there is a lack of government definitions and regulations for green cosmetics in the United States, the European Union and Brazil, and there are divergences between the guidelines adopted by green cosmetic certification systems, although we identified attempts to harmonize these guidelines. There was also a lack of approaches to the risk assessment of these products. The identification of limitations and perspectives on green cosmetics can be considered the first step to overcome these difficulties, promoting the dissemination of these products and maximizing their potential in reducing the risks to human and environmental health presented by cosmetics, following the principles of Green Chemistry.